2021
DOI: 10.3390/en14113076
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up Renewable Energy Assets: Issuing Green Bond via Structured Public-Private Collaboration for Managing Risk in an Emerging Economy

Abstract: Green bonds have increasingly been utilized around the world as a source of financing for renewable energy development, designed with compliance requirements and measurable economic returns to investors, while mitigating climate change. However, the efficacy of green bond arranged in the emerging economies for financing renewable energy assets and how the underlying risks are managed have remained to be explored. The paper aims to examine the evolving green financial system sponsored by both public and private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 32 publications
2
15
0
2
Order By: Relevance
“…A group of scholars showed that green finance is not an efficient tool in many countries because of various core problems. For instance, Fu and Ng ( 2021 ) and Hafner et al ( 2020 ) showed that green finance tools such as green bonds are inefficient in developing or less-developed economies because of the weak private sector and inappropriate financial infrastructure. Consistent with these studies, Hammoudeh et al ( 2020 ) attempted to find a link between green bonds and different economic and environmental indicators and concluded no causal link between green bonds and other variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A group of scholars showed that green finance is not an efficient tool in many countries because of various core problems. For instance, Fu and Ng ( 2021 ) and Hafner et al ( 2020 ) showed that green finance tools such as green bonds are inefficient in developing or less-developed economies because of the weak private sector and inappropriate financial infrastructure. Consistent with these studies, Hammoudeh et al ( 2020 ) attempted to find a link between green bonds and different economic and environmental indicators and concluded no causal link between green bonds and other variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers are concerned about green financing and energy efficiency. Eco-frie financing is not a viable option for many countries because of various underlying is Furthermore, the lack of private sector and insufficient financial infrastructure make g financing approaches like green bonds ineffective in developing or less developed na [13,14]. In line with earlier studies, Hammoudeh, Ajmi [15] investigated the relation between green bonds and various environmental and economic indicators and foun evidence of a causal association between them.…”
Section: Green Energy In the Asean Regionmentioning
confidence: 84%
“…The "renewable energies" cluster also refers to papers that analyse the impact of various non-financial drivers on development of the green bonds market: GDP per capital, CO 2 emissions and energy consumption in Nigeria [17]; economic infrastructure for public-private collaboration in the renewable energy sector [24]; macroeconomic, fiscal, and social-economic policies to change the flow of subsidies from fossil-fuel energy production to renewable ones [3]; and regulatory constraints about green energy and green finance [25].…”
Section: Renewable Energiesmentioning
confidence: 99%